(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article is written in the form of a letter, addressed the actor Bruno Araújo, a member of the Confraria da Serra group based at the Serra Azul I Penitentiary. The group is coordinated by Magno Bucci, who also, develops artistic activities with the group Mulheres de Atenas, at the Ribeirão Preto Women’s Penitentiary. Throughout he letter-article, we propose the differentiation of two forms of theatrical practice that take place inside the prison: Theater between Prisoners and Theater with Prisoners. Finally, we present some experiences developed by Bucci with prisoners, and we seek to value the artistic importance of theatrical events held in prison, both for the actors and the spectators.